Analisis Pengendalian Piutang Hotel Z Di Jakarta Pusat - Haryo Wicaksono; Anita Swantari; Filma Festivalia (Islamic University of Kalimantan MAB Banjarmasin, 2022)
The hotel industry is an industry that can support the tourism sector, including one-star to five-star hotels. This study aims to determine the development of receivables collection at Hotel Z Jakarta, where there are many variations of bad debts after 30 days. The research analysis method used is Accounts Receivable Turnover, Average Billing Period, Arrears Ratio, and Billing Ratio. The data obtained from this study uses the observation method of financial data, especially receivables data to analyze receivables in the 2019-2021 annual period to determine the level of receivables turnover on cash receipts. Based on the results of research conducted; The average billing period rate at the Hotel Z Jakarta hotel is still in good condition with an average of 18 days in paying off receivables. There is an increase of 13.48% in receivables collection from 2019-2021.